TRADITIONS AND RITUALS RELATED TO PARENTING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article reflects the rituals and rituals in the traditional culture of the Kyrgyz accompanying the process of raising a newborn child. It is shown that they are mainly based on folk knowledge and traditional beliefs formed as a result of long-term observations. It is noted that the child was considered the most important asset in Kyrgyz society, the rituals of the ancestors have not lost their relevance to this day.
Keywords: folk knowledge, joy, cradle, naming, traditional healing, beliefs, rituals.